TEACHERS’ CLASSROOM MANAGEMENT TECHNIQUES AT AL MADINAH ISLAMIC SCHOOL MAKASSAR - Asfah, Indrawaty; Akhmad, Fatmawati; Damayanti, Dwi (Media Inovasi Pendidikan dan Publikasi, 2024)
The teacher’s skill to manage a class is important. Class management is performed by teachers to create and maintain conducive classroom conditions that can enhance the teaching and learning process. This research aims at describing the teachers’ discipline dimension which is one of three dimensions in classroom management techniques. The research employs a qualitative approach by using questionnaire and focus group discussion. The findings showed that the discipline dimensions which consist of students’ involvement, reinforcement, verbal and nonverbal cues, and teacher-parents collaboration, all had been implemented by the teachers at Al MAdinah Islamic School. This has a direct impact on students’ academic success.